2020
DOI: 10.1111/1751-7915.13567
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing astaxanthin accumulation in Xanthophyllomyces dendrorhous by a phytohormone: metabolomic and gene expression profiles

Abstract: Xanthophyllomyces dendrorhous is a promising source of natural astaxanthin due to its ability to accumulate high amounts of astaxanthin. This study showed that 6-benzylaminopurine (6-BAP) is an effective substrate that enhances cell biomass and astaxanthin accumulation in X. dendrorhous. In the current study, the biomass and astaxanthin content in X. dendrorhous were determined to be improved by 21.98% and 24.20%, respectively, induced by 6-BAP treatments. To further understand the metabolic responses of X. de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 44 publications
1
61
1
Order By: Relevance
“…These results were not surprising since the glycolysis and PPP pathways could provide energy for cell growth and cofactors for carotenoid biosynthesis [ 15 ]. Facilitation of steroid and fatty acid for carotenoid accumulation has been well studied previously [ 16 ], and interestingly these pathways were also shown to be clustered in this study. In particular, as shown in Figure 2 C, most genes in the ergosterol biosynthetic pathway (ERG) containing ERG1 , ERG11 , ERG25 , ERG26 , ERG27 , ERG6 , ERG2 , ERG3 , ERG5 , and ERG4 were significantly upregulated in the YPM media.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These results were not surprising since the glycolysis and PPP pathways could provide energy for cell growth and cofactors for carotenoid biosynthesis [ 15 ]. Facilitation of steroid and fatty acid for carotenoid accumulation has been well studied previously [ 16 ], and interestingly these pathways were also shown to be clustered in this study. In particular, as shown in Figure 2 C, most genes in the ergosterol biosynthetic pathway (ERG) containing ERG1 , ERG11 , ERG25 , ERG26 , ERG27 , ERG6 , ERG2 , ERG3 , ERG5 , and ERG4 were significantly upregulated in the YPM media.…”
Section: Resultssupporting
confidence: 74%
“…The cell membrane of microorganisms contained a variety of sterols including ergosterol, fecosterol, and zymosterol [ 18 ]. Ergosterol played a key role in maintaining yeast membranes stabilization and was involved in carotenoid accumulation [ 16 ]. Besides, ergosterol biosynthesis showed facilitation for growth under ethanol stress [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analyses of the 594 amino acid sequence of crtYB from R. diobovata (AGT42003) with those from other Rhodotorula species, P. rhodozyma, S. salmonicolor , and S. pararoseus , revealed that the R. diobovata crtYB was most closely related to the crtYB of R. graminis WP1. An increase in the expression of this gene has been linked to increased carotenoid production in R. toruloides under light conditions [ 42 ], and it has been shown to be transcriptionally regulated in X. dendrorhous [ 43 ]. This gene is also one of the most favored in the engineering of noncarotenogenic yeast strains for the production of β-carotene [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, pyruvate and acetyl-CoA are also amino acid and fatty acids precursors, as well as substrates of the tricarboxylic acids cycle (Fig. 1 B) [ 51 ]. Although these substrates cannot be exclusively dedicated to the astaxanthin biosynthesis, it is possible to stress the yeast, either modulating the fermentation conditions or adding precursors and cofactors, to improve astaxanthin yields [ 30 , 49 ].…”
Section: Biosynthesis Of Astaxanthin In X Dendrorhousmentioning
confidence: 99%
“…Within the astaxanthin biosynthesis pathway, phytoene-β-carotene synthase ( crtYB ) is also a bottleneck for the accumulation of astaxanthin due to its low expression levels [ 33 , 55 – 58 ]. Similarly, low expression levels of cytochrome P450 reductase ( crtR ), which participates in the catalysis of the last step of the astaxanthin biosynthesis, have been observed [ 51 , 56 , 59 61 ]. Moreover, the biosynthesis of carotenoids is inactivated when catabolite repression is induced.…”
Section: Biosynthesis Of Astaxanthin In X Dendrorhousmentioning
confidence: 99%